2016
DOI: 10.5152/eurasianjmed.2015.0267
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Melatonin, Its Receptors and Drugs

Abstract: After a Turkish scientist took Nobel Prize due to his contributions to understand clock genes, melatonin, closely related to these genes, may begin to shine. Melatonin, a hormone secreted from the pineal gland at night, plays roles in regulating sleep-wake cycle, pubertal development and seasonal adaptation. Melatonin has antinociceptive, antidepressant, anxiolytic, antineophobic, locomotor activityregulating, neuroprotective, anti-inflammatory, pain-modulating, blood pressure-reducing, retinal, vascular, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(171 citation statements)
references
References 53 publications
(93 reference statements)
2
152
0
10
Order By: Relevance
“…Melatonin plays a regulatory role in a wide range of physiological and behavioral processes such as the sleep-wake cycle, seasonal adaptation, hormonal secretion, thermoregulation, reproduction, digestion, and many others. It also has antidepressant, neuroprotective, anti-inflammatory, and antioxidant effects [17]. …”
Section: Melatoninmentioning
confidence: 99%
“…Melatonin plays a regulatory role in a wide range of physiological and behavioral processes such as the sleep-wake cycle, seasonal adaptation, hormonal secretion, thermoregulation, reproduction, digestion, and many others. It also has antidepressant, neuroprotective, anti-inflammatory, and antioxidant effects [17]. …”
Section: Melatoninmentioning
confidence: 99%
“…Synthetic compounds derived from MLT have been studied so that the analysis of structure-activity relationship enhance the understanding of receptors and the antioxidant mechanism in the different pathological conditions reported in the literature, including liver dysfunctions [70][71].…”
Section: Immunohistochemistry Of Tnf-αmentioning
confidence: 99%
“…Cloning studies identified three subtypes of membrane melatonergic receptors: MT1 receptors which are expressed in the suprachiasmatic nucleus of the hypothalamus and pars tuberalis of the pituitary, MT2 mainly located in brain and retina, and MT3 receptors which are not expressed in mammals but were found in fish, amphibians, birds and chickens [10]. MT1 and MT2 receptors were found in rodent testis including mice, rats and hamsters [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…MT1 and MT2 receptors were found in rodent testis including mice, rats and hamsters [11][12][13][14]. Melatonin also exerts its effects by binding to orphan nuclear receptors (the retinoid-related orphan nuclear hormone receptor RZR/RORα and the X-linked melatonin-related orphan receptor GPR50) and intracellular proteins such as calmoduline [10].…”
Section: Introductionmentioning
confidence: 99%